Essential spectra of operator matrices and applications. (19th June 2013) - Charfi, Salma; Jeribi, Aref; Moalla, Rihab
<x xml:space="preserve">Abstract</x> The main goal of this paper is to give a characterization of Wolf, Schechter, and Browder essential spectra of (2 × 2) matrix operator on a Banach space. Furthermore, we apply the obtained results to transport equations. Copyright © 2013 John Wiley & Sons, Ltd.